THE DETERMINATION OF OPINIONS ON PREFERENCES OF HEALTH SCIENCES STUNDENT ON THE MODE OF DELIVERY - Doganer, Gulbahtiyar; Doganer, Adem; Duran, Ozlem; Tuna, Merve; Tezcan, Serife; Turan, Gulcin (Galenos Yayincilik, 2013)
Aim: This study was done to determine the preferences of health sciences students on the mode of delivery. Materials and methods: The sampling of this descriptive study is 555 students (260 medical students, 204 nursing students, 91 midwifery students) who have taken the courses on giving birth and gynecological diseases at Cumhuriyet University. All the data were collected by a questionnaire form consisting 19 questions which were prepared and developed by the researchers. All the questions were asked by using structured interview technique. The colleced data were analyzed and evaluated by SPSS (ver: 13.0) as chi-square test, digits, percentage. Findings: The mode of delivery was mostly prefered as normal vaginal in %88.5 and most part of this preference is of the nursing students as % 92.6. % 60.3 of the students prefer normal delivery system because it is natural. % 83.8 of the students studying in the faculties of medical sciences are against to make caesarean delivery voluntarily without any indication. % 96.8 of them think that gender of the baby doesn't affect the delivery form. % 99.5 of the participants think that the caesarean delivery system is highly expensive. Some medical students (%23.8) think that optional caesarean section can be done even without any medical indications. Whereas, most of the health students (%73.9) think that epidural anaesthesia should be done during the normal vaginal delivery. Result: The health sciences students prefer normal vaginal delivery and have the thought that epidural anaesthesia should be done to decrease the pain during this mode of delivery.
Sa?lik bi?li?mleri?nde okuyan ö?renci?leri?n do?um şekli? terci?hleri?ne yöneli?k düşünceleri?ni?n beli?rlenmesi?
Keywords: caesarean section; delivery mode; health sciences students; normal vaginal delivery